Rebels with a Cause: Does Ideology Make Armed Conflicts Longer and Bloodier?. (November 2022) - Basedau, Matthias; Deitch, Mora; Zellman, Ariel
Ideology may directly provide motive and indirectly capacity for collective violence, thus making armed conflicts longer and bloodier. We investigate these propositions by drawing on an innovative global dataset which codes ideological claims by rebel groups and governments in intrastate armed conflicts since 1946. Results demonstrate that although ideology increases conflict duration, these effects vary by type and timing. Whereas secular ideological conflicts tended to be more protracted during the Cold War, religious ideology has become increasingly important since. We, however, find little evidence that ideology increases conflict intensity. Rather, rebel criminality best accounts for intensity. So, while immaterial resources like ideology sustain willingness to fight, ideology's influence upon conflict intensity is limited, especially after the Cold War. Future studies need to take ideology seriously and need to investigate its characteristics more in-depth and in conjunction with material, identity related and international variables.